Some aspects of skilled personnel optimization in conditions of informatization - Gramudin. L. Abdulgalimov (Высшее образование в России)
Optimization of skilled personnel in conditions of global informatization is the main focus of the article. The matter concerns training of IT-related specialists for solving the applied ITproblems in particular professional sphere. The training system for bachelor of applied information technology should include the algorithms and logic training and should take into account the new FSES and the requirements of information society.